Handover From the Emergency Department to Inpatient Units: A Quality Improvement Study. Issue 4 (October 2021) - Tobiano, Georgia; Ryan, Christine; Jenkinson, Kim; Scott, Lucie; Marshall, Andrea P.
Abstract : Background: Intrahospital handovers are high risk. Standardization of content and process is recommended. Local Problem: Emergency department to inpatient unit handovers were inefficient. Interventions: The intervention was a standardized operating protocol, including checklist and procedures. Methods: The intervention was coproduced and prototyped. Handovers were observed for intervention adherence, and the Handover Evaluation Scale was used to measure nurses' perceived quality of handover. Results: The handover had 3 steps. Step 1 had more content, prompting by the receiver, and family participation postintervention. Step 3 was shorter in duration, had less content, and occurred at the bedside more postintervention. Receiving nurses were able to ask questions and found that information provided was timely, current, and easy to follow. Sending nurses perceived that handover was less succinct postimplementation, despite decreases in handover duration and repetition of information. Conclusions: This project has triggered ongoing improvement initiatives, necessary to keep accommodating the needs of nurses that work across boundaries. Abstract : Supplemental Digital Content is Available in the Text.